A clinical study of outcome of two different methods of meatoplasty following modified radical mastoidectomy - Surbhi; Shaheen Zafar; Rohit Kumar (Asian Journal of Medical Sciences, 2022)
Background: Meatoplasty usually is the final step of a canal wall down mastoidectomy. It provides sufficient enlargement of the external auditory meatus which leaves the patient with a smaller mastoid recess that could readily be cleaned and examined without anatomical restriction. Aims and Objectives: The aims of this study were to study the outcome of two different methods of meatoplasty following modified radical mastoidectomy. Materials and Methods: This is a prospective study done for 2 years from January 2020 to December 2021 on 50 patients of chronic otitis media unsafe type, where modified radical mastoidectomy was done followed by meatoplasty. Results: The result in both the groups is comparable up until the meatus remains wide and large which could facilitate cavity examination, aeration, debridement, and drainage. Conclusion: Outcome was favorable in both the groups and complications related to the meatoplasty technique was also comparable.